Employment Tactics and Strategies of Technical-Vocational Education Students for Career and Professional Development in the Labour Market of Vietnam - Thuan Kieu, Quan; Kirya, Mateeke Moses; Liu, Wei-Te (Journal of Technical Education and Training, 2023)
Many policies and strategies have been implemented to improve both the quality and quantity of Vietnam's technical and vocational education (TVE) system, and the results indicated innovative reform of the TVE system in both ways in Vietnam. Many aspects of TVE in Vietnam have been explored by a series of reports of the National Institute for Vocational Education and Training (NIVET); however, there exists a shortage of studies attempting to focus on the process of TVE graduates’ employment experience in the Vietnamese labour market. This study attempts to explore the employment of TVE graduates from technical colleges in Vietnam, with a focus on their employment tactics. To base this study on a qualitative approach, the primary data sources were obtained through semi-structure interviews and self-diary on employment tactics and strategies of TVE graduates in the labour market within two years. The obtained data were subjected to thematic analysis. Based on this, results revealed difficulty in obtaining desirable and high-paying jobs even though it was not difficult to obtain jobs to earn a living. Also, low satisfaction and resilience due to poor working conditions were revealed. Three key strategies: maintaining low pay jobs to earn a living, updating their skills to get better jobs, and changing to suitable jobs were figured out by TVE graduates. These strategies gradually assisted TVE graduates to obtain sustainable goals of career promotion and professional development.